2022
DOI: 10.1038/s41598-022-21995-7
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic activity of pomegranate rind extract and Zn (II) against Candida albicans under planktonic and biofilm conditions, and a mechanistic insight based upon intracellular ROS induction

Abstract: Candida albicans (C. albicans) is an opportunistic pathogen, which causes superficial infection and can lead to mortal systemic infections, especially in immunocompromised patients. The incidence of C. albicans infections is increasing and there are a limited number of antifungal drugs used in treatment. Therefore, there is an urgent need for new and alternative antifungal drugs. Pomegranate rind extract (PRE) is known for its broad-spectrum antimicrobial activities, including against C. albicans and recently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 74 publications
1
5
1
Order By: Relevance
“…The UPLC test showed the presence of α-punicalagin and β-punicalagin with two almost similar peaks in the UV spectrum compared to the positive control. This result corroborates with the findings by Celiksoy et al, who found two similar punicalagin peaks in the UPLC chromatogram [ 16 ]. However, the total amount of phenolic content was different between researchers.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The UPLC test showed the presence of α-punicalagin and β-punicalagin with two almost similar peaks in the UV spectrum compared to the positive control. This result corroborates with the findings by Celiksoy et al, who found two similar punicalagin peaks in the UPLC chromatogram [ 16 ]. However, the total amount of phenolic content was different between researchers.…”
Section: Discussionsupporting
confidence: 93%
“…The polyphenolic and tannin compounds (as the punicalagin) promote the antimicrobial activity of the PGE through the precipitation of proteins on the cell surface of the microorganism and inhibiting metabolic enzymes that cause cell lysis [ 16 , 28 ]. The preparation method and chemical characterization of tested extracts are essential because their activity is directly affected by the plant part, plant age, season of collection, drying strategy, and extraction procedure [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations